Internal control of maintenance expenses of an educational institution in the Lambayeque region 2021 - Torres Ventura, Rosa del Pilar (2023)
An analysis of the internal control of maintenance expenses was conducted in an educational institution, using a quantitative and descriptive non-experimental design approach, with a cross-sectional type. A convenience non-probabilistic sample was selected, composed of workers from administrative areas. Literature from authors such as Álvarez-Sanango et al. (2020), Bakhtigozina et al. (2018), Bermeo-Giraldo et al. (2021), Carrillo et al. (2021), and Cevallos Villegas et al. (2018), among others, was consulted. A survey was used and a Likert scale form was applied, with 29 printed items, in a face-to-face interview. The results showed that 76.85 % of the workers reported a stable and secure organizational culture, with practices based on ethical values, effective communication, and a clear assignment of responsibilities, which favored a good organizational climate. Additionally, it was possible to identify how risk management was being carried out in 76.04 %, with clear and transparent goals that allowed analyzing the probability of fraud and taking necessary measures to mitigate risks. Finally, 79.77 % of the workers stated that the institution continuously supervised and monitored processes, activities, and tasks to achieve objectives. In conclusion, efforts were made to improve internal control, which will greatly contribute to a correct and adequate distribution of maintenance expenses.